Habitat Characteristics and Population of Javan Langur (Trachypithecus Auratus E. Geoffroy Saint-Hilaire, 1812) In Leuweung Sancang Nature Reserve, Garut, West Java - Abdul Haris Mustari; Achmad Fajar Pasaribu (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2019)
This study aimed to determine habitat characteristics, food plants, population size, and distribution of Javan langur in Leuweung Sancang Nature Reserve. This study was conducted from February to April in Leuweung Sancang Nature Reserve. Composition and structure of vegetation were determined using vegetation analysis. Population and distribution of the javan langur were identified using concentration count method. A total of 110 plant species recorded in the javan langur’s habitat. Ketapang (Terminalia catappa) was the dominant species in the study area composing 41,71% of the IVI. The Javan langur feed on at least 17 plant species. The plant parts eaten by the Javan langur included leaves, buds, shoots, flowers and fruits. A total of 19 javan langur groups were encountered along the beach forest of the nature reserve. Number of individual at each of the group varied ranging from 7 to 17 individuals. The population size was 227 individuals and the population density was 0.15 individuals per hectare. The javan langur’s age structure of adult : young : juvenile was 43 %: 27 %: 30 % indicating that the population was dominated by adult individuals and the sex ratio of male:female was 1:3. Keywords: food plants, habitat, population, Trachypithecus auratus